Feasibility and usefulness of tele-follow-up in the patients with tuberculous meningitis. (24th May 2021) - Kalita, Jayantee; Pandey, Prakash C; Shukla, Ruchi; Misra, Usha K
Abstract: Background: Tuberculous meningitis (TBM) is the most severe form of tuberculosis and these patients need close follow-up because of a high frequency of complications. The coronavirus disease 2019 pandemic and lockdown resulted in an interruption in physical follow-up. In this situation, tele-follow-up may be helpful. We report the feasibility and usefulness of a telephonic follow-up in patients with TBM. Methods: Patients with TBM managed by us from January 2017 to March 2020 were included from the TBM registry. Their presenting symptoms, and clinical and investigation findings were noted. We contacted these patients telephonically and their clinical status was obtained using a questionnaire. Based on the telephonic information, outcomes were categorized as death, poor or good. Patients with the new medical problems were advised as to relevant investigations and the reports were obtained through WhatsApp for prescribing treatment. Results: The telephone numbers of 103 of 144 (71.5%) patients were viable. Twenty-seven (26.2%) patients died, 15 (19.7%) had a poor outcome and 61 (80.2%) had a good outcome. Twenty-five (32.9%) patients had new medical problems: 18 TBM related and 7 TBM unrelated. The medical problems of 23 patients could be managed telephonically and only 3 (4%) patients needed a physical visit. Sixty-five (85.5%) patients happily answered the questionnaire and willing responders needed a treatment modification more frequently than the reluctant responders (p=0.008). Patients on active antitubercular treatment needed treatment modification more frequently (80% vs 21.3%). Conclusions: Tele-follow-up is feasible in 96% of TBM patients and is beneficial, cost effective and overcomes the barrier of distance.